Study on Glass-Epoxy-Based Low-Cost and Compact Tip-Truncated Triangular Printed Antenna - Rajeev Kumar Kanth; Pasi Liljeberg; Hannu Tenhunen; Qiang Chen; Lirong Zheng; Harish Kumar (International Journal of Antennas and Propagation)
Printed antennas based on glass epoxy substrate have been developed. On the basis of required specifications and assigned frequencies, tip-truncated triangular printed antennas have been designed, analyzed, and fabricated. The performances of the antennas have been measured in terms of return loss, frequency of operation, bandwidth, and radiation pattern. Triangular microstrip antenna (TMSA) configuration consisting of copper as active radiating patch and glass epoxy as dielectric substrate has been screened out to achieve the essential characteristics and satisfying recommended low-cost antenna. The Method of Moment (MOM) analyzing techniques have been employed to realize the required specific properties, whereas optimized tip truncation technique and varying feed point location give rise to suitable LHCP or RHCP configuration of the printed antenna. The coaxial probe signal feed arrangement have been considered for this work. The proposed printed antennas are suitable for communication links between ships or buoys and satellites specially for navigation purpose.